Murine AKAP7 Has a 2′,5′-Phosphodiesterase Domain That Can Complement an Inactive Murine Coronavirus ns2 Gene - Elona Gusho (American Society for Microbiology, 2014)
ABSTRACT Viral 2′,5′-phosphodiesterases (2′,5′-PDEs) help disparate RNA viruses evade the antiviral activity of interferon (IFN) by degrading 2′,5′-oligoadenylate (2-5A) activators of RNase L. A kinase anchoring proteins (AKAPs) bind the regulatory subunits of protein kinase A (PKA) to localize and organize cyclic AMP (cAMP) signaling during diverse physiological processes. Among more than 43 AKAP isoforms, AKAP7 appears to be unique in its homology to viral 2′,5′-PDEs. Here we show that mouse AKAP7 rapidly degrades 2-5A with kinetics similar to that of murine coronavirus (mouse hepatitis virus [MHV]) strain A59 ns2 and human rotavirus strain WA VP3 proteins. To determine whether AKAP7 could substitute for a viral 2′,5′-PDE, we inserted AKAP7 cDNA into an MHV genome with an inactivated ns2 gene. The AKAP7 PDE domain or N-terminally truncated AKAP7 (both lacking a nuclear localization motif), but not full-length AKAP7 or a mutant, AKAP7H185R, PDE domain restored the infectivity of ns2 mutant MHV in bone marrow macrophages and in livers of infected mice. Interestingly, the AKAP7 PDE domain and N-terminally deleted AKAP7 were present in the cytoplasm (the site of MHV replication), whereas full-length AKAP7 was observed only in nuclei. We suggest the possibility that viral acquisition of the host AKAP7 PDE domain might have occurred during evolution, allowing diverse RNA viruses to antagonize the RNase L pathway. IMPORTANCE Early virus-host interactions determine whether an infection is established, highlighting the need to understand fundamental mechanisms regulating viral pathogenesis. Recently, our laboratories reported a novel mode of regulation of the IFN antiviral response. We showed that the coronavirus MHV accessory protein ns2 antagonizes the type I IFN response, promoting viral replication and hepatitis. ns2 confers virulence by cleaving 2′,5′-oligoadenylate (2-5A) activators of RNase L in macrophages. We also reported that the rotavirus VP3 C-terminal domain (VP3-CTD) cleaves 2-5A and that it may rescue ns2 mutant MHV. Here we report that a cellular protein, AKAP7, has an analogous 2′,5′-phosphodiesterase (2′,5′-PDE) domain that is able to restore the growth of chimeric MHV expressing inactive ns2. The proviral effect requires cytoplasmic localization of the AKAP7 PDE domain. We speculate that AKAP7 is the ancestral precursor of viral proteins, such as ns2 and VP3, that degrade 2-5A to evade the antiviral activity of RNase L.